P05.64 The disease burden of meningioma patients: long-term results on work productivity and healthcare consumption. (19th September 2018) - Zamanipoor Najafabadi, A H; van der Meer, P B; Boele, F W; Reijneveld, J C; Taphoorn, M J B; van Furth, W R; Dirven, L; Peerdeman, S M; ,
Abstract: Background: Meningioma patients suffer from short- and long-term neurological sequelae and impaired health-related quality of life (HRQoL). However, it is unknown how these impairments affect patients' work productivity and healthcare consumption on the long-term. Material and Methods: In a multicentre cross-sectional study intracranial meningioma patients of working age (18–67 years) at a median of 10.0 years after anti-tumour therapy were included. Patients completed a validated questionnaire on work productivity (SF-HLQ), and a study-specific questionnaire on healthcare consumption. One-sample t-test was used to compare meningioma patients with normative data of the Dutch population. Generalised linear models were used to compare meningioma patients with a control population, corrected for: age, sex, educational level and comorbidity. Patient recruitment and data collection is still in progress. Results: 106 meningioma patients were included (mean age: 57.7 years, WHO grade I: 93.5%, surgery: 94.2%, radiotherapy: 17.5%). Meningioma patients had a paid job in 48.1% of cases, compared with 71.8% of the Dutch population of working age (p<0.001). More patients reported obstacles at work (49.1%) than controls (n=72, 20.9%, p=0.003). These problems at work included concentration problems (sometimes: 40.0%, often: 28.0%, always: 8.0%), slower work pace (sometimes: 36.0%, often: 36.0%, always: 12.0%), feeling of isolation (sometimes: 12.0%, often: 12.0%, always: 0.0%), delaying work (sometimes: 52.0%, often: 16.0%, always: 4.0%), and the need for someone to take over their work (sometimes: 33.3%, often: 4.2%, always: 4.2%). Furthermore, on the long-term, specialised healthcare consumption (i.e. outpatient clinic visits) was significantly higher in meningioma patients (70.4%) compared with controls (49.5%, p=0.003). Conclusion: Meningioma patients have less often a paid job when compared to the average Dutch population. Moreover, those patients having paid work report more obstacles, particularly concentration problems and a slower work pace. Therefore, employment issues in meningioma should receive more attention, even up to 10 years after intervention.